The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1516-89132009000500029
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in the gill and liver tissues of freshwater fish, Cirrhinus mrigala exposed to dichlorvos

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 21 publications
8
38
1
Order By: Relevance
“…The observed pathological changes after butachlor treatment in the gills of rainbow trout are in agreement with reports in other fish species treated with different pollutants (Cengiz and Unlu 2003;Altinok and Capkin 2007;Velmurugan et al 2009;Ahmed et al 2013). This is perhaps because of the direct contact of gills with the toxin.…”
Section: Discussionsupporting
confidence: 91%
“…The observed pathological changes after butachlor treatment in the gills of rainbow trout are in agreement with reports in other fish species treated with different pollutants (Cengiz and Unlu 2003;Altinok and Capkin 2007;Velmurugan et al 2009;Ahmed et al 2013). This is perhaps because of the direct contact of gills with the toxin.…”
Section: Discussionsupporting
confidence: 91%
“…; b -lamellar lifting in gills, exposed to 6.6 mg/L thiamethoxam, 400X; c -edema in gills, exposed to 6.6 mg/L thiamethoxam, 400X; d -proliferation of glandular cells and filamentous epithelium ( ) in gills, exposed to 10 mg/L thiamethoxam, 400X; e -fusion in gills, exposed to 20 mg/L thiamethoxam, 400X; f -degenerative alterations in gills, exposed to 10 mg/L thiamethoxam, 400X; g -degenerative alterations in gills, exposed to 10 mg/L thiamethoxam, 400X; h -vasodilatation in blood vessels of secondary lamellae in gills, exposed to 6.6 mg/L thiamethoxam, 400X; i -vasodilatation in gill filament blood vessels, exposed to 6.6 mg/L thiamethoxam, 400X. Lamellar lifting, edema and filamentous epithelial proliferation are histopathological alterations, which have been described by other authors who investigated the effects of pesticide contamination on aquatic species (Cengiz and Unlu 2002;Cengiz 2006;Velmurugan et al 2009). Similarly to the present results, they found that these changes were the most frequent in the gill histological structure under the influence of different pesticides.…”
Section: Resultsmentioning
confidence: 74%
“…We saw pufferfish burrowed in the sand or wedged between rocks or urchins presumably in attempts to remain submerged, and sediment damage might have contributed to gill pathology. Epithelial chan ges in the gills can be caused by a variety of insults (Velmurugan et al 2009), and toxins can cause lamellar collapse (Mallatt 1985). We are less sure of the origin of rosettes within primary lamellae, as this pathology has not been described before in finfish.…”
Section: Discussionmentioning
confidence: 99%